UK biobank: an open access resource for identifying the causes of a wide range of complex diseases of middle and old age. - Cathie Sudlow (PLoS Medicine, 2015)
Cathie Sudlow and colleagues describe the UK Biobank, a large population-based prospective study, established to allow investigation of the genetic and non-genetic determinants of the diseases of middle and old age.